Task-Related Deactivation and Functional Connectivity of the Subgenual Cingulate Cortex in Major Depressive Disorder - Davey, Christopher G.; Yücel, Murat; Allen, Nicholas B.; Harrison, Ben J. (Frontiers in Psychiatry, 2012)
Background: Major depressive disorder is associated with functional alterations in activity and resting-state connectivity of the extended medial frontal network. In this study we aimed to examine how task-related medial network activity and connectivity were affected by depression. Methods: Eighteen patients with major depressive disorder, aged 15- to 24-years-old, were matched with 19 healthy control participants. We characterised task-related activations and deactivations while participants engaged with an executive-control task (the multi-source interference task; MSIT). We used a psycho-physiological interactions (PPI) approach to examine functional connectivity changes with subgenual ACC. Voxelwise statistical maps for each analysis were compared between the patient and control groups. Results: There were no differences between groups in their behavioral performances on the MSIT task, and nor in patterns of activation and deactivation. Assessment of functional connectivity with the subgenual cingulate showed that depressed patients did not demonstrate the same reduction in functional connectivity with the ventral striatum during task performance, but that they showed greater reduction in functional connectivity with adjacent ventromedial frontal cortex. The magnitude of this latter connectivity change predicted the relative activation of task-relevant executive control regions in depressed patients. Conclusions: The study reinforces the importance of the subgenual cingulate cortex for depression, and demonstrates how dysfunctional connectivity with ventral brain regions might influence executive–attentional processes.